A performance comparison between polyurethane and ceramic densifying cyclones, K.C. Naidoo - K. C. Naidoo (The Southern African Institute of Mining and Metallurgy, 2020)
There are two main types of densifying cyclones currently available in the market, namely polyeurethane (PU) and ceramic. The PU densifying cyclones are currently used throughout the Grootegeluk complex and coal beneficiation in general. It has been identified that PU densifiers wear relatively fast depending on the operating pressure and need to be replaced frequently as a result. The motivation for this paper is to achieve an increase in the densifying cyclone lifetime through less wear and an increase in efficiency resulting in the ability to build higher relative densities (RD) more quickly. This will allow for a reduction in downtimes due to replacing densifying cyclones as well as building RD and a reduction in the operating costs associated with replacing worn densifying cyclones. Some of the major findings of the study indicated that the ceramic cyclone theoretically undergoes less wear than the PU cyclone, but since wear is application-specific and was evaluated, the wear on the polyurethane cyclone was found to be minimal. The RD differential is higher on the PU cyclones than the ceramic cyclones, showing that the PU cyclones perform better in a densifying application. This is the first test conducted on this application and type of cyclones. It should therefore be noted that having the PU cyclone significantly outperform the ceramic cyclone was not expected, due to the only change being the material of construction. This is an indication to take the material of construction into account when selecting cyclones as it can have a significant impact on the cyclone performance in specific applications. Keywords: Ceramic, cyclone, densifying, density, dense medium, polyurethane, wear